Money and finance in East and West - Saunders, Christopher Thomas; The Vienna Institute for Comparative Studies (Wien ; New York : Springer-Verlag, 1978)
"Contains the proceedings of the fourth in a series of international workshops concerned with problems of East-West economic interaction in Europe, organized by the Vienna Institute for Comparative Studies ... [and] held in October 1977 in Budapest."
Workshop papers volume 4.
Includes bibliographical references.
hza 20/02/2019
Loans
Keywords: International finance; Money; Finance; East-West trade